Micro-structure analysis of magnesium alloy and its nanocomposite on temperature effect - Koh, Vincent Wei Sheng. (2013)
Magnesium alloys (AZ-series) have been attracting much attention as the lightest structural materials which led to the combination of magnesium and silicon carbide nanoparticles (AZ-SiC series) to create a new kind of nanocomposite, commonly known as Metal Matrix Composites (MMCs). A legitimate scientific study is not done to look at the change in microstructure and composition of AZ31B and AZ31B-1vol%SiC after high strain rate (3000±200/s) Split Hopkinson Pressure Bar testing at -30°C & 25°C. Microscopy techniques such as Optical Microscopy (OM), Scanning Electron Microscope (SEM) and Electron Dispersive Spectrum (EDS) was being utilised to look at the microstructure and composition of the material. From stress-strain curve obtained after high strain rate compression testing, the fracture point in AZ31B for -30°C specimen and 25°C specimen is 0.335mm/mm and 0.355 mm/mm respectively. The ultimate strength (compressive) in in AZ31B for -30°C specimen and 25°C specimen is 295 MPa and 305 MPa respectively. The fracture point in AZ31B-1vol%SiC for -30°C specimen and 25°C specimen is 0.280mm/mm and 0.305/mm respectively. The ultimate strength (compressive) in AZ31B-1vol%SiC for -30°C specimen and 25°C specimen is 460 MPa and 440 MPa respectively. Grain size measurement on average is about 78 μm for AZ31B and 75 μm for AZ31B-1vol%SiC. AZ31B and AZ31B-1vol%SiC revealed cracks with branching for both 25°C and -30°C specimens after compression testing. Volume of twins in -30°C specimen is greater as compared to 25°C specimen upon compression testing in AZ31B-1vol%SiC. The microstructure of the AZ31B alloy consists of fine porosities and α-Mg hcp matrix and β-Mg₁₇Al₁₂ second phase. The microstructure of the AZ31B-1vol%SiC alloy consists of fine porosities and α-Mg hcp matrix and Mg₂Si second phase. Reasonably uniform distribution of SiC nanoparticles can be observed. Overall, SiC nanoparticles did play an important role in grain refinement of AZ31B.